(untitled) (International Journal of Architecture and Urbanism, 2024)
The current research is mainly targeting the major challenge of climate change and flood risk in Indonesia (Jakarta) through investigations on suitable methods of sustainable urban drainage systems (SUDS). Through climate scenarios and flood risk assessments, as well as SUDS efficiency appraisals, this study aims at helping stakeholders gain insight on innovative water management strategies. The combination of hydrological models, GIS analysis, and stakeholdersâ€™ engagement is the research approach that will enable the exploration of Jakarta’s vulnerability to extreme weather events and introduce mitigation techniques in the form of SUDS. This study aims to address climate changeâ€™s impact on flood risk and develop sustainable design solutions so that the infrastructure in Jakarta can be resilient to flooding. The findings of this research are to provide a basis for decisions, plans, and policies towards green water management regulations and a more water-resilient urban built environment.